Colônia de férias de Olinda: presos políticos e aparelhos de repressão em Pernambuco (1964) - Silva, José Rodrigo de Araújo (2013)
This work aims to study the structure of political repression in the state of Pernambuco in 1964. In order to do this, we take as a documental case study, a detention unit with the specific purpose of housing political prisoners, called "Colônia de Férias de Olinda" (Olinda Summer Camp). We seek to understand - using the methods of documentary research and oral history how was the articulation of this unit with the other organs of that state security in the complex network of information in that military government established in the country. We also propose to study administrative inner workings of the Summer Camp, to reveal the strategies and mechanisms used by the agents of repression at the time of arrests, to describe the profile of individuals who passed through the unit, and to find evidences of traumatic memory in the testimony of those who directly or indirectly have had contact with the Olinda Summer Camp.